The epidemiology of medium chain acyl Co-A dehydrogenase deficiency - Ali, Sikander; Bano, Atia; Sayyed, Sadaf (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
The impairment in the ability of human body due to a disorder in the Fatty Acid Oxidation (FAO) results in the incomplete breakdown of medium chain fatty acids into Acetyl Co-A caused by the deficiency of an enzyme MCAD. When this enzyme is deficient, fatty acids can’t be broken down into acetyl Co-A rather they tend to accumulate within certain organs such as brain and liver leading to various serious disorders. MCAD deficiency is an inherited, rare metabolic disease. The diagnosis of MCAD is done by integrated interpretation of multiple analysis, requires the clinical status of the individual that is affected. Testing of MCADD is done by the analysis of Plasma acyl carnitine, testing of organic acid and acyl glycine in urine and then, confirmatory testing is performed. Genetic counselling must be provided to affected individuals, carriers, or the individuals that are at danger of becoming carriers.